Differentiation at work, K-5 : principles, lessons, and strategies - Narvaez, Lane, 1951- (Corwin, 2010)
With information for administrators and authentic tools for teachers, this hands-on resource demonstrates how student achievement increases when an entire school focuses on making differentiation work.